The Investigation of Total Trihalomethanes Concentration in Drinking Water in Al-Dora and Al-Rasheed plants in Baghdad - Asaad, Nasma; Al-Azzawi, Muhamad; Mohammed, Ahmad (Iraqi Journal of Science, 2023)
During period from September 2012 to August 2013, concentration of total Trihalomethanes (TTHMs) was assessed in drinking water in Al-Dora and Al-Rasheed purification plants. 216 samples were collected from final basins of chlorination in purification plants and from sites that distributed among residential areas fed by the project. TTHMs concentration did not exceed (0.15 ppm) which is the maximum limits according to Iraqi standard specification for drinking water. The highest value was in July (0.12 ppm) and the lowest value was in November (0.01 ppm).